2022
DOI: 10.3390/cancers14225718
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Quality Assessment in Breast Cancer: Implications for Fertility Preservation

Abstract: Background: The aim of this study was to evaluate the effects of breast cancer on the ovarian response and on oocyte quality following controlled ovarian hyperstimulation (COH). Methods: This retrospective case-control study evaluated the effects of breast cancer on the ovarian response and on the oocyte quality. Oncological patients with breast cancer undergoing controlled ovarian stimulation cycles for fertility preservation, and age- and date-matched controls undergoing COH for in vitro fertilization (IVF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…High levels of AMH affect the quality and number of follicles and provide better fertility rates [10]. In many studies, it was observed that AMH levels and AFC were affected by chemotherapy and decreased significantly with treatment [8,10,17]. In our study, the AMH and AFC values were significantly decreased during follow-up in breast cancer patients who received adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…High levels of AMH affect the quality and number of follicles and provide better fertility rates [10]. In many studies, it was observed that AMH levels and AFC were affected by chemotherapy and decreased significantly with treatment [8,10,17]. In our study, the AMH and AFC values were significantly decreased during follow-up in breast cancer patients who received adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the continuation of fertility may be more likely in patients with high pre-treatment AMH levels. Ovum cryopreservation is the most commonly used method for the prevention of fertility [8,15,17,20]. Although there is limited information in the literature, the rate of healthy infants is 20-30% in ovarian cryopreservation and is dependent on the age and ovarian reserve of the oncology patients [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also suggested that breast cancer is associated with poor oocyte quality without impairment of ovarian reserve. 35 In addition, factors influencing the oocyte quality, such as age, body mass index, AMH, breast cancer stage, breast cancer gene (BRCA) status, and hormone receptors, were not significantly associated with dysmorphic oocytes. Therefore, that study concluded that breast cancer is the only risk factor for dysmorphic oocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Some anomalies may be attributed to intrinsic factors such as genetic background and patient's age, while others seem to be related to the suboptimal intrafollicular environment (e.g., oxidative stress, hypoxia, proapoptotic factors, inflammation, and hyperglycemia). Recently breast cancer was identified as a risk factor for the presence of dysmorphic oocytes (29). This evidence suggests that alteration of hormonal receptors and/or signaling pathways might impair follicleoocyte dialogue and compromise the quality of developing female gametes.…”
Section: Discussionmentioning
confidence: 99%